Computational Study of Linear and Nonlinear Optical Properties of Single Molecules and Clusters of Organic Electro-Optic Chromophores - Garrett, Kerry Ellen (My University, 2016)
Organic electro-optic (OEO) materials integrated into silicon-organic hybrid (SOH) devices afford significant improvements in size, weight, power, and bandwidth (SWAP) performance of integrated electronic/photonic systems critical for current and next generation telecommunication, computer, sensor, transportation, and defense technologies. Improvement in molecular first hyperpolarizability, and in turn electro-optic activity, is crucial to further improvement in the performance of SOH devices. The timely preparation of new chromophores with improved molecular first hyperpolarizability requires theoretical guidance; however, common density functional theory (DFT) methods often perform poorly for optical properties in systems with substantial intramolecular charge transfer character. The first part of this dissertation describes the careful evaluation of popular long-range correction (LC) and range-separated hybrid (RSH) density functional theory (DFT) for definition of structure/function relationships crucial for the optimization of molecular first hyperpolarizability, β. In particular, a benchmark set of well-characterized OEO chromophores is used to compare calculated results with the corresponding experimentally measured linear and nonlinear optical properties; respectively, the wavelength of the peak one-photon absorption energy, λmax, and β. A goal of this work is to systematically determine the amount of exact exchange in LC/RSH-DFT methods required for accurately computing these properties for a variety OEO chromophores. High-level electron correlation (post-Hartree-Fock) methods are also investigated and compared with DFT. Included are results for the computation of β using second-order Møller-Plesset perturbation theory (MP2) and the double-hybrid method, B2PLYP. The second part of this work transitions from single-molecule studies to computing bulk electronic and nonlinear optical properties of molecular crystals and isotropic ensembles of a high-β chromophore, YLD124. Of particular interest are phenomena such as aggregation and the effect of intermolecular interactions on EO activity.
Thesis (Ph.D.)--University of Washington, 2015-12
Keywords: Aggregation; Computational Chemistry; Density Functional Theory; Electro-optics; Hyperpolarizability; Nonlinear Optics; Chemistry; Theoretical physics; Materials Science; chemistry